(S)-1-(Pent-4′-enoyl)-4-(hydroxymethyl)-azetidin-2-one derivatives as inhibitors of human fatty acid amide hydrolase (hFAAH): synthesis, biological evaluation and molecular modelling. (October 2014) - Caruano, Joséphine; Feledziak, Marion; Labar, Geoffray; Michaux, Catherine; Perpète, Eric A.; Muccioli, Giulio G.; Robiette, Raphaël; Marchand-Brynaert, Jacqueline
Abstract A series of lipophilic ester derivatives (2a–g) of (S)-1-(pent-4′-enoyl)-4-(hydroxymethyl)-azetidin-2-one has been synthesised in three steps from (S)-4-(benzyloxycarbonyl)-azetidin-2-one and evaluated as novel, reversible, β-lactamic inhibitors of endocannabinoid-degrading enzymes (human fatty acid amide hydrolase (hFAAH) and monoacylglycerol lipase (hMAGL)). The compounds showed IC50 values in the micromolar range and selectivity for hFAAH versus hMAGL. The unexpected 1000-fold decrease in activity of 2a comparatively to the known regioisomeric structure 1a (i.e. lipophilic chains placed on N1 and C3 positions of the β-lactam core) could be explained on the basis of docking studies into a revisited model of hFAAH active site, considering one or two water molecules in interaction with the catalytic triad.